2013
DOI: 10.1111/mmi.12371
|View full text |Cite
|
Sign up to set email alerts
|

The N‐terminal region of the NeurosporaNDR kinase COT1 regulates morphology via its interactions with MOB2A/B

Abstract: Summary Nuclear Dbf2p-related (NDR) protein kinases are important for cell differentiation and polar morphogenesis in various organisms, yet some of their functions are still elusive. Dysfunction of the Neurospora crassa NDR kinase COT1 leads to cessation of tip extension and hyperbranching. NDR kinases require the physical interaction between the kinase’s N-terminal region (NTR) and the MPS1-binding (MOB) proteins for their activity and functions. To study the interactions between COT1 and MOB2 proteins, we m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Images were recorded and processed using the NIS‐Elements F package (a software developed by Nikon Corporation, Japan). Hyphal branching was quantified as described by Carmit Ziv et al ., ().…”
Section: Methodsmentioning
confidence: 97%
“…Images were recorded and processed using the NIS‐Elements F package (a software developed by Nikon Corporation, Japan). Hyphal branching was quantified as described by Carmit Ziv et al ., ().…”
Section: Methodsmentioning
confidence: 97%
“…The images were recorded and processed using the NIS-Elements F package (Nikon Corporation, Japan). Hyphal branching was quantified according to Ziv et al (2013).…”
Section: Measurement Of the Distance Between G Lucidum Mycelium Branmentioning
confidence: 99%
“…Based on their phenotype as well as their physical interactions with COT1, it has been suggested that MOB2A and MOB2B may have many overlapping functions (Maerz et al ., ). Nonetheless, we have previously established the fact that there are differences in the strength of the physical interactions between COT1 and the two MOB proteins and that MOB2B, but not MOB2A, is involved in negative control of asexual conidial production via the COT1 pathway (Maerz et al ., ; Ziv et al ., ). Thus, while overlapping functions exist, under certain conditions, the two proteins lack compensatory capabilities.…”
Section: Introductionmentioning
confidence: 97%
“…The N. crassa COT1 protein and its homologues in other fungi have been shown to regulate hyphal elongation and branching (Yarden et al ., ; Buhr et al ., ; Dürrenberger and Kronstad, ; Mcnemar and Fonzi, ; Scheffer et al ., ; Johns et al ., ; Ziv et al ., ; Kodama et al ., ). While evidence for the role of phosphorylation concerning the function of COT1 and other NDR kinases has accumulated (Millward et al ., ; Mah et al ., ; Emoto et al ., ; Hou et al ., ; Stegert et al ., ; Ziv et al ., ), no evidence for potential phosphorylative regulation of MOB proteins in N. crassa has been provided to date. Nonetheless, phosphorylative regulation of MOB proteins in other systems has accumulated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation